Tracing the urbanisation of risk in Malawi: A multilevel analysis - Bauer, Willi; Titz, Alexandra; Manda, Mtafu C. (Jàmbá, 2024)
Cities in Malawi have long been outside the focus of disaster risk reduction. As a result, urban risks remain poorly understood, and urban governments and disaster risk reduction (DRR) practitioners working in cities struggle to adequately support vulnerable urban populations. This is evidenced by recent disasters such as Cyclone Freddy, which devastated the city of Blantyre in 2023, and increasingly common small-scale events in urban areas. This article analyses the Malawian city as a distinct riskscape, shaped by national-level policies of neglect that create an institutional void that DRR practitioners working at the city level struggle to fill. This process is complicated by a multitude of challenges at different levels of governance, especially leaving small-scale events prevalent in urban areas largely unaddressed. This process of risk accumulation is increasingly affecting urban residents. Methodologically, we demonstrate this through a comprehensive policy analysis and by drawing on expert and civil society interviews and questionnaires conducted in Lilongwe City. Contribution: By outlining the interlocking challenges at multiple levels and grounding them in empirical data, we highlight the specificities of urban DRR efforts in Malawi and provide opportunities to improve them.
CRIS-Team Scopus Importer:2024-09-20
Keywords: disaster risk reduction; global south; governance; Malawi; multilevel analysis; urban vulnerability